Dr. Juro Adlešič, župan "velike Ljubljane" (1935-1942) - Šorn, Mojca (Studia Historica Slovenica, 2017)
In this disquisition, the authors take a look at the work of Juro Adlešič, who governed Ljubljana as mayor for the second half of the 1930s (until the outbreak of the war in Yugoslavia) and even beyond, during the Italian occupation after 1941. In the introduction, we establish that Adlešič, as his predecessors, was not elected mayor according to the principle of democratic electoral choice, but on the basis of the fact that his political party, the Slovenian People's party, assumed power in Belgrade as part of the state-wide Yugoslav Radical Union. In the main part, we analytically expose that his term as the head of Ljubljana was one of the more fruitful, which was due to three external reasons: (a) favorable financial-economic circumstances, (b) favourable political circumstances, (c) in 1935 Ljubljana expanded territorially.
Keywords: Adlešič, Juro; Ljubljana; lokalna samouprava; Slovenija; zgodovina; župani